2013
DOI: 10.1097/bsd.0b013e318232313d
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility Analysis of Minimally Invasive Versus Open Multilevel Hemilaminectomy for Lumbar Stenosis

Abstract: MIS versus open multilevel hemilaminectomy was associated with similar cost over 2 years while providing equivalent improvement in QALYs. In our experience, MIS versus open multilevel hemilaminectomy is a cost equivalent technology for patients with lumbar stenosis-associated radicular pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Another study by Parker et al evaluating MISS versus open multilevel hemilaminectomy showed similar results with a cost savings of $628 in direct costs and $1683 in indirect costs (> 2.5 times more savings in indirect costs). 17 This further exemplifies the impact of indirect costs in determining whether MISS is truly more cost-effective than open spine surgery and the need for more studies reporting indirect costs. Allen and Garfin discussed the potential of MISS to increase societal productivity as patients have a quicker recovery, shorter LOS, and faster return to work, which, theoretically, will all result in lower indirect costs for MISS patients and increased societal productivity.…”
Section: Discussionmentioning
confidence: 92%
“…Another study by Parker et al evaluating MISS versus open multilevel hemilaminectomy showed similar results with a cost savings of $628 in direct costs and $1683 in indirect costs (> 2.5 times more savings in indirect costs). 17 This further exemplifies the impact of indirect costs in determining whether MISS is truly more cost-effective than open spine surgery and the need for more studies reporting indirect costs. Allen and Garfin discussed the potential of MISS to increase societal productivity as patients have a quicker recovery, shorter LOS, and faster return to work, which, theoretically, will all result in lower indirect costs for MISS patients and increased societal productivity.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, VAS pain scores were significantly lower in MIS cohorts at final follow-up. From a cost perspective, Parker et al determined that functional gain and costs were equivalent between open and MIS approaches for multilevel hemilaminectomy [20]. Quality-adjusted life years (QALYs) gained was 0.72 for both approaches, while the 2-year total cost was similar for both open ($25,420) and MIS cohorts ($23,109).…”
Section: Degenerative Spinal Stenosis: Mis Lumbar Decompressionmentioning
confidence: 99%
“…One 11 used data from a prospective cohort. [11][12][13][14] The generalizability of included studies to broader clinical populations needs to be considered. Explicit details on economic modeling, including related assumptions and justifi cation for the economic model chosen, were rarely described.…”
Section: Study Selection and Qualitymentioning
confidence: 99%
“…One US cost-utility study 13 retrospectively compared open versus MAS multilevel hemilaminectomy in patients (n = 54) with multilevel lumbar stenosis corresponding to radicular symptoms ( Tables 2 and 3 ). There was no baseline difference between groups.…”
Section: Hemilaminectomy Of the Lumbar Spinementioning
confidence: 99%